A botanist's guide to parties and poisons [large type] - Khavari, Kate (Khavari, Kate. Saffron Everleigh mystery, 2024)
"Newly minted research assistant Saffron Everleigh is determined to blaze a new trail at the University College London, but with her colleagues' beliefs about women's academic inabilities and not-so-subtle hints that her deceased father's reputation paved her way into the botany department, she feels stymied at every turn. When she attends a dinner party for the school, she expects to engage in conversations about the university's large expedition to the Amazon. What she doesn't expect is for Mrs. Henry, one of the professors' wives, to drop to the floor, poisoned by an unknown toxin. Dr. Maxwell, Saffron's mentor, is the main suspect and evidence quickly mounts. Joined by fellow researcher -- and potential romantic interest -- Alexander Ashton, Saffron uses her knowledge of botany as she explores steamy greenhouses, dark gardens, and deadly poisons to clear Maxwell's name. Will she be able to uncover the truth, or will her investigation land her on the murderer's list, in this entertaining examination of society's expectations?"--